Demographic, socioeconomic, and sociocultural factors associated with any breastfeeding in homeless mothers - Pauline Frenoy; Stéphanie Vandentorren; Amandine Arnaud; Cécile Vuillermoz; Raquel Rico Berrocal; Judith Martin‐Fernandez; Elie Azria; Blandine deLauzon‐Guillain; Jonathan Y. Bernard; Sandrine Lioret (Wiley, 2021)
Abstract In high‐income countries, breastfeeding has been shown to be positively associated with socioeconomic position. However, less is known about breastfeeding practices and their associated factors among extremely disadvantaged populations. We aimed to assess the associations of cultural origins and socioeconomic factors with any breastfeeding initiation and duration in homeless families. We analyzed data from 456 children aged 6 months to 5 years from the cross‐sectional ENFAMS survey, conducted in 2013 among a random sample of homeless families in shelters in the Greater Paris area. Data were collected by bilingual interviewers in 17 languages. Four nested multivariable robust Poisson regression models were run in a hierarchical framework to determine the factors associated with breastfeeding initiation and with any breastfeeding for 6 months or more. Most of the children (86.0%) had previously been or were currently being breastfed at the time of the survey; 58.9% were fed with breast milk ≥6 months. A higher maternal age and African origin were positively associated with breastfeeding ≥6 months, although the relation to the region of origin was moderated by education level. Migration to escape war, unrest or other violence and the child's birth in France were inversely associated with breastfeeding ≥6 months. Any breastfeeding by these homeless mothers seems influenced predominantly by their cultural origin and complicated by a difficult migration trajectory. The possible influence of poor material circumstances and cumulative hardship should encourage interventions targeted at homeless mothers that emphasize social/family support with a commitment to improving the family's living conditions.